71.0k views
4 votes
Wx+yz=bc , solve for z .

User Nilbert
by
7.3k points

2 Answers

6 votes

Answer:

The solution for the provided equation for z is
z=(bc-wx)/(y).

Explanation:

Consider the provided equation.

wx+yz=bc

We need to solve the above equation for z.

Subtract both the side by wx.


wx+yz-wz=bc-wx


yz=bc-wx

Now isolate the variable z by dividing both side with y.


(yz)/(y)=(bc-wx)/(y)


z=(bc-wx)/(y)

Hence, the solution for the provided equation for z is
z=(bc-wx)/(y).

User Snieguu
by
7.0k points
2 votes
wx+yz=bc
minus wx on both sides
yz=bc-wx
dividing 'y' on both sides
Hence,
z=(bc-wx)/y
Here is what you need.
Hope it helped
User BruceCui
by
7.3k points